2021
DOI: 10.1111/aor.14058
|View full text |Cite
|
Sign up to set email alerts
|

Defining and understanding the “extra‐corporeal membrane oxygenation gap” in the veno‐venous configuration: Timing and causes of death

Abstract: In-hospital mortality of adult veno-venous extracorporeal membrane oxygenation (V-V ECMO) patients remains invariably high. However, little is known regarding timing and causes of in-hospital death, either on-ECMO or after weaning. The current review aims to investigate the timing and causes of death of adult patients during hospital admittance for V-V ECMO, and to define the V-V ECMO gap, which is represented by the patients that are successfully weaned of ECMO but still die during hospital stay. A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…However, 10.4% (11 of 106) of these patients died in the ICU after ECMO weaning and decannulation. A similar finding was published in a systemic review by Heuts et al [ 26 ], where 12.7% of the deceased patients died in the ICU after VV-ECMO weaning and before discharge. Similar results were recently published by Lorusso et al [ 9 ] in large, multi-national COVID-19 ECMO patient group, where they reported 19% in-hospital mortality after ECMO weaning and 50% overall in-hospital mortality.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, 10.4% (11 of 106) of these patients died in the ICU after ECMO weaning and decannulation. A similar finding was published in a systemic review by Heuts et al [ 26 ], where 12.7% of the deceased patients died in the ICU after VV-ECMO weaning and before discharge. Similar results were recently published by Lorusso et al [ 9 ] in large, multi-national COVID-19 ECMO patient group, where they reported 19% in-hospital mortality after ECMO weaning and 50% overall in-hospital mortality.…”
Section: Discussionsupporting
confidence: 87%
“…Instead, they are surrogates for critical illness and indeed, signify a worse prognosis. Inevitably, whenever required, CVVH combined ECMO therapy is effective and should be established [ 11 , 25 , 26 ]. Sepsis will sooner or later develop in many patients under prolonged ICU stay, although reports of bacteremia in COVID-19 patients on ECMO are scarce and lack statistical power [ 2 , 3 , 4 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other potential causes include bleeding complications, sepsis, multiple organ failure, etc. [20,21]. Right ventricular contractile support, pulmonary vasodilators, diuretics, and inodilators may be utilized as adjunctive therapies.…”
Section: Results Basic Informationmentioning
confidence: 99%
“…The most frequent complications and one of the common causes of death for patients on ECMO are thrombus formation and bleeding [ 5 , 6 ]. The risk of bleeding is related to patient-specific and treatment-related factors associated with ECMO.…”
Section: Introductionmentioning
confidence: 99%